The Role of MreB, MreC and MreD in the Morphology of the Diazotrophic Filament of Anabaena sp. PCC 7120 - Cristina Velázquez-Suárez; Ignacio Luque; Antonia Herrero (Life, 2022)
The cyanobacterium Anabaena sp. PCC 7120 forms filaments of communicating cells. Under conditions of nitrogen scarcity, some cells differentiate into heterocysts, allowing the oxygen-sensitive N2-reduction system to be expressed and operated in oxic environments. The key to diazotrophic growth is the exchange of molecules with nutritional and signaling functions between the two types of cells of the filament. During heterocyst differentiation, the peptidoglycan sacculus grows to allow cell enlargement, and the intercellular septa are rebuilt to narrow the contact surface with neighboring cells and to hold specific transport systems, including the septal junction complexes for intercellular molecular transfer, which traverse the periplasm between heterocysts and neighboring vegetative cells through peptidoglycan nanopores. Here we have followed the spatiotemporal pattern of peptidoglycan incorporation during heterocyst differentiation by Van-FL labeling and the localization and role of proteins MreB, MreC and MreD. We observed strong transitory incorporation of peptidoglycan in the periphery and septa of proheterocysts and a maintained focal activity in the center of mature septa. During differentiation, MreB, MreC and MreD localized throughout the cell periphery and at the cell poles. In mreB, mreC or mreD mutants, instances of strongly increased peripheral and septal peptidoglycan incorporation were detected, as were also heterocysts with aberrant polar morphology, even producing filament breakage, frequently lacking the septal protein SepJ. These results suggest a role of Mre proteins in the regulation of peptidoglycan growth and the formation of the heterocyst neck during differentiation, as well as in the maintenance of polar structures for intercellular communication in the mature heterocyst. Finally, as previously observed in filaments growing with combined nitrogen, in the vegetative cells of diazotrophic filaments, the lack of MreB, MreC or MreD led to altered localization of septal peptidoglycan-growth bands reproducing an altered localization of FtsZ and ZipN rings during cell division.